The Impact of Regional Competitiveness on GRDP: Mediating Roles of Unemployment and Poverty in Indonesia - Harsono, Pramudi; Istiqomah; Gunawan , Diah Setyorini (International Journal of Accounting and Economics Studies, 2025)
This research aims to investigate the impact of regional competitiveness on Gross Regional Domestic Product (GRDP) in Indonesia, focusing on the mediating roles of unemployment and poverty in this relationship. The study seeks to provide insights into how enhancing re-‎gonial competitiveness can influence economic growth while addressing critical socioeconomic issues. Methodology: A mixed-methods ‎approach was employed, combining quantitative and qualitative data. Quantitative data were sourced from secondary reports, including ‎those from BPS and the World Bank, covering 34 Indonesian provinces from 2010 to 2022. Statistical analyses, including regression and ‎correlation, were conducted to examine the relationships between regional competitiveness, GRDP, unemployment, and poverty. Qualitative ‎data were collected through surveys and in-depth interviews to enrich the understanding of the quantitative findings. The findings indicate ‎that regional competitiveness positively affects GRDP, particularly through factors such as infrastructure and institutional development. ‎However, the influence of human resources, market factors, and innovation ecosystems on GRDP is significantly reduced when poverty ‎and unemployment are considered as intervening variables. This highlights the complex interplay between these factors. The study concludes that while enhancing regional competitiveness is crucial for economic growth, it must be coupled with effective strategies to reduce ‎poverty and unemployment. Policymakers are encouraged to focus on strengthening regional infrastructure and institutions to optimize ‎GRDP outcomes. Future research should explore additional indicators of competitiveness and sector-specific impacts to further inform ‎regional development strategies in Indonesia‎.